The Relationship between Internalized Stigma, Perceived Social Support and Self-Efficacy in Bipolar Disorder - ÖZDAMAR ÜNAL, Gülin; ÖNAL, Bektaş; İŞCAN, Gökçe; ATAY, İnci (Genel tip dergisi, 2022)
Objectives: Many people with mental illness are subject to social and objective exclusion, discrimination, and stigma. One of the mental illnesses most exposed to stigma is bipolar disorder (BD). This study aimed to ascertain patient perceptions of social support and examine the association between internalized stigma, self-esteem, and clinical course in patients with bipolar disorder. Method: This cross-sectional study enrolled 103 patients with BD. Sociodemographic form, Internalized Stigma of Mental Illness Inventory (ISMI), Rosenberg Self-Esteem Scale (RSE), Multidimensional Scale of Perceived Social Support (MSPSS) were used to collect data in this study. Results: The mean age of 103 patients with BD was 40,67±10,53. 46 (44.7%) of these participants were female. The ISMI score was higher in patients who were unemployed than in those who were employed (p=0.050). In terms of ISMI scores, those with residual symptoms had significantly higher scores than those without (p=0,001). The ISMI scores of those whose medication was inconsistent were significantly higher than those who were compliant with their medication (p=0.004). ISMI had a positive correlation between the number of depressions (p<0.001; r=0.243); medication non-adherence (p<0.001; r=0.282). ISMI had negative correlation between RSE (r=-0.711; p<0,001); MSPSS (r=-0,384; p<0,001). In multivariate linear regression, internalized stigma was significantly higher among those with low self-esteem, those who reported a lower level of social support from their friends, and those with residual symptoms. Conclusions: The link between stigma, self-esteem, and social support, and their effects on patients with BD, have important implications for psychiatric care. Direct interventions to reduce the negative effects of stigma in BD deserve clinical attention as they may potentially improve outcomes. Amaç: Akıl hastalığı olan birçok insan, sosyal ve nesnel dışlanmaya, ayrımcılığa ve damgalanmaya maruz kalmaktadır. Damgalanmaya en çok maruz kalan ruhsal hastalıklardan biri bipolar bozukluktur (BB). Bu çalışmanın amacı, BB hastalarının içselleştirilmiş damgalamalarını belirlemek ve algılanan sosyal destek, benlik saygısı ve klinik değişkenler arasındaki ilişkiyi ortaya koymaktır. Gereç ve yöntem: Bu kesitsel çalışma BB tanılı 103 hasta ile yürütülmüştür. Bu çalışmada veri toplamak için sosyodemografik form, Ruhsal Hastalıkların İçselleştirilmiş Damgalanması Envanteri (ISMI), Rosenberg Benlik Saygısı Ölçeği (RSE), Çok Boyutlu Algılanan Sosyal Destek Ölçeği (MSPSS) kullanılmıştır. Bulgular: 103 hastanın yaş ortalaması 40.67±10.53 idi. Bu katılımcıların 46'sı (%44.7) kadındı. ISMI puanı, işsiz olanlarda bir işte çalışanlardan daha yüksekti (p=0.050). ISMI skorları açısından rezidüel semptomları olanlar, olmayanlara göre anlamlı olarak daha yüksek skorlara sahipti (p=0.001). İlaçlarını uyumsuzluğu olanların ISMI puanları, ilaçlarına uyumlu olanlara göre anlamlı olarak daha yüksekti (p=0.004). Depresyon sayısı (p<0.001; r=0.243) ve ilaç uyumsuzluğu (p<0.001; r=0.282) ile ISMI arasında pozitif korelasyon vardı. ISMI skoru ile RSE (r=-0.711; p<0.001) ve MSPSS (r=-0.384; p<0.001) arasında ise negatif korelasyon vardı. Çok değişkenli lineer regresyon analizinde düşük benlik saygısına sahip olanlar, arkadaşlarından daha düşük düzeyde sosyal destek bildirenler ve rezidüel semptomları olanlar arasında içselleştirilmiş damgalanma anlamlı olarak daha yüksekti. Sonuç: Damgalama, benlik saygısı ve sosyal destek arasındaki bağlantı ve bunların BB hastaları üzerindeki etkileri psikiyatrik bakım için önemli çıkarımlara sahiptir. Bipolar bozuklukta damgalanmanın olumsuz etkilerini azaltmaya yönelik doğrudan müdahaleler, hastalık sonuçlarını iyileştirme potansiyeline sahip olabileceğinden klinik olarak göz önünde bulundurulmalıdır.